The Role of Philosophy of Science in the Development of Science - Reza Aulia Setiawan; Sofyan Sauri (al-Afkar, Journal For Islamic Studies, 2024)
Philosophy of science is often considered a separate field and even irrelevant to the development of science. This assumption is a big mistake. This paper aims to reveal the role of philosophy of science in the three stages of scientific development (justification of initial concepts, integration of new theories, and criticism of scientific results) and to identify which philosophical approaches contribute most to the progress of science. Through a review of contemporary literature, it is found that the philosophy of science always provides an important rational basis for fundamental scientific conceptions, guides the direction of scientific development, bridges various scientific disciplines and approaches, and criticizes scientific theories and paradigms that are considered established. The rationalism and empiricism approaches have been identified as the most dominant and monumental in their role in shaping modern scientific methodology to date. Thus, the claim regarding the fundamental role of philosophy of science in the history and future of science has been proven comprehensively.